Analisis Kelayakan Teknis dan Finansial Usahatani Kelapa Sawit di Desa Epeesi Kecamatan Basala Kabupaten Konawe Selatan - Selviana Selviana; Abdi Abdi; Waode Yusria (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2022)
This research aims to determine the technical feasibility of oil palm farming in Epeesi Village, Basala District. Knowing the financial feasibility of oil palm farming in Epeesi Village, Basala District. The implementation of this research will start from October 2021 to December 2021. The research variables are the respondent farmers' identity and the farming actors' characteristics. This research uses qualitative and quantitative methods. The data in this study were analyzed using the costs used for production, production revenue and net income, technical feasibility analysis and financial feasibility analysis. Based on the results of the study, it was found that the processing of oil palm plantations in Epeesi Village, Basala District, South Konawe Regency, in terms of technical aspects, was feasible in the category of land suitability, growing conditions, production processes, the technology used for transportation of oil palm and oil palm production capacity. Palm oil farming is financially feasible to operate with an NPV value of IDR747.570.637,- > one feasible and IRR to produce an interest rate of 70.58%, which is a higher than the amount of interest that has been set with a value of 8.58%. A Net Benefit Cost Ratio of 12.04 > 1 is categorized as feasible, and the PP is three years and six mounts. The price decrease that occurred in the sensitivity analysis with a value of 10% and 30%, as well as an increase in production costs by 10% and 30%, so that the investment return period is below the economic time of farming, which is eight years, so based on the financial feasibility criteria, oil farming palm worth working on.